Bile Salt Degradation by Nonfermentative Clostridia - Mahony, David E. (Appl Environ Microbiol, 1977)
Eight strains of nonfermentative clostridia were characterized on the basis of their intracellular nicotine adenine dinucleotide- and nicotinamide adenine dinucleotide phosphate-dependent hydroxysteroid dehydrogenase (HSDH) content, ability to deconjugate taurocholate, growth characteristics, and metabolic products, including utilization of lactate and pyruvate. Two cultures of Clostridium sporosphaeroides (representing one strain obtained from two different sources), one strain of Clostridium irregularis, four strains of an unnamed species (Clostridium group SPH-1), and one strain of an unnamed species (Clostridium group P) were studied. Both cultures of C. sporosphaeroides contained low amounts of 7α-HSDH; C. irregularis contained only a low amount of 3α-HSDH. All four strains of Clostridium SPH-1 contained both 12α- and 7α-HSDH in the ratio of approximately 10:1. The strain of Clostridium group P contained only 12α-HSDH and was devoid of any other bile salt oxidoreductases. The enzyme preparation from Clostridium group P was useful in spectrophotometric quantitative studies of 12α-OH groups. Correlation of bile salt degradative activities with other phenotypic tests for characterization of and differentiation among such organisms is discussed. IMAGES: